2012
DOI: 10.2486/indhealth.2012-0009
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Pressure Pain in the Upper Trapezius Muscle, Cervical Range of Motion, and the Cervical Flexion^|^ndash;relaxation Ratio after Overhead Work

Abstract: This study examined the changes in pressure pain in the upper trapezius muscle, cervical range of motion, and cervical flexion-relaxation ratio after overhead work. 14 workers were recruited. Pressure pain in the upper trapezius muscle, active cervical range of motion, and cervical flexion-relaxation ratio were measured in all subjects once before and once after overhead work. The pressure-pain threshold of the left upper trapezius muscle was 8.6 ± 2.5 lb before overhead work and 7.3 ± 2.4 lb after overhead wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Shin et al reported that the cervical FRR on the left side was 1.3 ± 0.2 before and 1.1 ± 0.2 after overhead work; the respective values for the right side were 1.4 ± 0.5 and 1.2 ± 0.3, revealing a similar decrease with overhead work 20) . Lee et al suggested that the cervical FRR is a quantitative way to evaluate the potential for developing neck pain with heavy backpack loads.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Shin et al reported that the cervical FRR on the left side was 1.3 ± 0.2 before and 1.1 ± 0.2 after overhead work; the respective values for the right side were 1.4 ± 0.5 and 1.2 ± 0.3, revealing a similar decrease with overhead work 20) . Lee et al suggested that the cervical FRR is a quantitative way to evaluate the potential for developing neck pain with heavy backpack loads.…”
Section: Discussionmentioning
confidence: 90%
“…Shin et al reported that active CROM decreased after overhead work 20) . Shin and Yoo reported that active CROM decreased after video display terminal work 21) .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the thoracic FRR decreased significantly in sequence from pre-work, to overhead work, to below-knee work. Shin et al found that cervical FRRs on both sides decreased significantly after 10 min of overhead work 3 ) . Lee et al found that wearing heavy backpacks decreased cervical FRR 5 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The FRR was found to be reduced after the Sorenson protocol was used to induce neck pain fatigue in 20 healthy participants. The effect of various activities on the cervical FRP has been reported including carrying a backpack, 22 working on a computer, 23 overhead work, 24 visual display terminal work, 25 and below-knee assembly work. 2 Pialasse et al 26 have reported on the effects of load and speed on the cervical FRP.…”
Section: Introductionmentioning
confidence: 99%